Histological and immunohistochemical approaches to molecular subtyping in muscle-invasive bladder cancer - Attanasio, Giulio; Failla, Maria; Poidomani, Simone; Buzzanca, Tindaro; Salzano, Serena; Zizzo, Maurizio; Palicelli, Andrea; Zanelli, Magda; Koufopoulos, Nektarios; Russo, Giorgio Ivan; Caltabiano, Rosario; Broggi, Giuseppe (Frontiers in Oncology, 2025)
Muscle-invasive bladder cancer (MIBC) is an aggressive form of bladder cancer, representing 20–25% of all bladder cancer cases. Characterized by invasion into the detrusor muscle, MIBC often leads to high rates of metastasis and poor outcomes, with five-year survival rates below 50% for localized disease and less than 15% for metastatic cases. MIBC primarily affects older adults, especially men, with smoking and chemical exposure being the leading risk factors. Clinically, MIBC presents significant heterogeneity, both histologically and molecularly, making diagnosis and management challenging. Histological variants of MIBC, such as squamous, micropapillary, plasmacytoid, and neuroendocrine subtypes, are associated with distinct prognoses and variable treatment responses. Recent advances in genomic profiling have identified molecular subtypes of MIBC—luminal, basal/squamous, neuronal, and stroma-rich—each with unique biological characteristics and treatment sensitivities. Despite these advancements, the widespread adoption of molecular profiling is hindered by the high costs and limited availability of these technologies, particularly in resource-limited settings. As a result, there is an increasing need for alternative, more accessible diagnostic methods to predict molecular subtypes. In this context, histological examination combined with immunohistochemical markers, such as GATA3, KRT5/6, and p63, has been shown to reliably correlate with molecular subtypes and guide therapeutic decisions. This review presents a comprehensive analysis of how histology, immunohistochemistry and molecular subtyping can be integrated into routine clinical practice to inform treatment strategies for MIBC, providing a pathway toward more personalized and effective management.